Three Translucency Heat-treatment of Two Ceramic CAD Milling Blocks and their Effect on Leakage and Film Thickness - Amal Abdallah A. Abo-Elmagd,; Noha Mohammed, (International Journal of Medical Toxicology and Legal Medicine, 2024)
This study aims to evaluate and compareleakage and film thickness when applying three translucency heat-treatment to two CAD Milling blocks(Emax CAD and Amber Mill) considering temperature and holding time for translucency heat-treatment.120 cemented laminate veneers were randomly divided into two groups, Group 1: (Amber Mill, N=60), and Group 2: (Emax CAD, N=60). Then, they were divided into 3 subgroups, based on thermal temperature. the measurements of film thickness and leakage were applied.a two-way ANOVA was used. Student's t-test was used to compare between two materials.It has been found that the firing cycles and translucency levels had a significant effect on both leakage and film thickness.The degree of translucency and direction of manufacturing during firings has direct effect on both film thickness and leakage. there is a direct relationship between increasing the degree of translucency of Amber Mill and leakage and film thickness.